2013
DOI: 10.1002/chem.201301659
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic Elucidation of the Inhibitory Mechanism of Cys2His2 Zinc Finger Transcription Factors by Cobalt(III) Schiff Base Complexes

Abstract: Transcription factors are key regulators in both normal and pathological cell processes. Affecting the activity of these proteins is a promising strategy for understanding gene regulation and developing effective therapeutics. CoIII Schiff base complexes ([Co(acacen)(L)2]+ where L = labile axial ligands) have been shown to be potent inhibitors of a number of zinc metalloproteins including Cys2His2 zinc finger transcription factors. Inhibition by [Co(acacen)(L)2]+ of the target protein is believed to occur thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
28
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 39 publications
(78 reference statements)
3
28
0
Order By: Relevance
“…A cobalt (III) Schiff base complexe ([Co(acacen)(NH 3 ) 2 ] + ) has been shown to inhibit C 2 H 2 zinc finger transcription factors non-specifically. To enhance the specificity, an E-box DNA oligonucleotide specifically targeting Snail was attached to the acacen equatorial ligand 77 . This Co(III)-E-box complex was a potent inhibitor of Snail- mediated transcriptional repression in breast cancer cells and in the neural crest of Xenopus 78 .…”
Section: Epithelial To Mesenchymal Transition (Emt) In Pancreatic Canmentioning
confidence: 99%
“…A cobalt (III) Schiff base complexe ([Co(acacen)(NH 3 ) 2 ] + ) has been shown to inhibit C 2 H 2 zinc finger transcription factors non-specifically. To enhance the specificity, an E-box DNA oligonucleotide specifically targeting Snail was attached to the acacen equatorial ligand 77 . This Co(III)-E-box complex was a potent inhibitor of Snail- mediated transcriptional repression in breast cancer cells and in the neural crest of Xenopus 78 .…”
Section: Epithelial To Mesenchymal Transition (Emt) In Pancreatic Canmentioning
confidence: 99%
“…Other transcription factors have been targeted by similar strategies based on directly or indirectly preventing protein:protein or protein:DNA interactions. For example, S3I‐201 prevents the dimerization of Stat3 and the binding of Stat3 to DNA , and Co III Schiff base complexes can alter the structure of zinc fingers, which are a common feature of transcription factors, and selectively disrupt their DNA‐binding ability .…”
Section: What Are the Implications For Targeting Myc In Cancer Therapmentioning
confidence: 99%
“…It was also demonstrated that in neutral samples Hg(II) can completely replaces Zn(II) in these complexes. 323 Because of the possible redox reactions and concomitant complex formation Cu(II) ions are also potential inhibitors of zinc finger peptides. The results were simulated by a multisite binding model with a significant interaction between them.…”
Section: Metal Complexes Of Peptide Fragments Of Prion Proteinmentioning
confidence: 99%